Artificial Intelligence and Smart Society: Educational Applications, Emergences and Issues – A Scientific Review - Paul, P.K. (International Journal of Applied Science and Engineering (India), 2023)
Artificial Intelligence is one of the alarming and important term and concept these days, and dedicated in advancing general Information Technology operations, it is dedicated to developing intelligence in the systems and the same can be applicable in various products and services. Artificial Intelligence in short called as Al and basically performed by various kind of machines and systems, in general using Al machine act like humans and also able to mimic their actions; further, it is able to learning and problem-solving affairs. As far as core types are concerned Weak Artificial Intelligence is needed in designing of the system for a particular job whereas Strong Artificial Intelligence is able to perform duties like humans and able in more complex and complicated system development. Thus Strong Al complex and complicated and basically solve the problem without having a person. Machine Learning is important sub set of Artificial Intelligence and also depends on various statistical techniques and other parts of computation, decision making, etc. Al and allied technologies such as Robotics, Deep Learning, Machine Learning, etc., are important subcomponents and fields helps in educational development and process. Today face-to-face education i.e. traditional education including online education highly depends on Al and Allied Technologies.